(untitled) (Al-Qamar, 2020)
In Islamic Republic of Pakistan principles of Bioethics are essential to be incorporated in the medical system. This descriptive research elaborates the concept, scope and application of conventional and Islamic bioethical principles in Pakistani perspective. Comparative and analytical methodologies of research have been applied evaluating the conventional as well as the Islamic norms and principles in Pakistani context. Starting from the general meaning of the term Bioethics to its concept in Sharī‘ah perspective this investigation extends to the practical steps taken by the Islamic Republic of Pakistan for the incorporation of Islamic principles of Bioethics. The issue of Ethical Review has been examined keeping in view its historical perspective and current procedure. It ends with the recommendations for the implementation of the Islamic principles of Bioethics and reformation of the review system, modification of the curricula and training of the medical practitioners.